เอกโซพอลิแซ็กคาไรด์จากแล็กติกแอซิดแบคทีเรียและการประยุกต์ในน้ำสลัด - วิชชุดา วิไลรัศมี (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
In the present study, exopolysaccharide (EPS) producing-lactic acid bacteria (LAB) were isolated from Thai fermented vegetables with eight isolates; L01 – L08 were obtained. Chemical and Physical properties of EPSs were study the results of which revealed that EPSs from L01–L08 possessed similar properties of consisting glucose, partly soluble while L07 was totally soluble. All EPSs showed low viscosity and low water holding capacity. These EPSs displayed as good emulsifying activity as xanthan gum. The highest EPS producers were isolate L06 and L07 at 11.20 and 11.40 g/l, respectively. Thus, L06 and L07 were selected for further studies. Taxonomic studies and 16S rDNA analysis classified isolate L06 and L07 as member of genus Weissella. Further characterization demonstrated that EPSs from L06 and L07 did not form gel, neutral charge, were able to form good flocculation and form emulsion in olive oil with good stability, able to with hold high temperature, good antioxidant, exhibiting a non-Newtonian pseudoplastic behavior with molecular weight of 2.8 x10³ and 3.3 x10³ Dalton, respectively. EPS from isolate L06 and L07 (0.4% w/v) was employed as ingredient in salad dressing along with olive oil. The salad dressing obtained particle sizes of 2.44 and 2.92 micrometer for L06 and L07, respectively and able to stabilize such emulsion for 1 day. Judging from the above properties, EPS from strain L06 and L07 with their indicated emulsifying properties and emulsion stabilization made them suitable for application in food.